Autopsy of Ajaokuta Steel Rolling Mills Functioning with Emphasis on Equipment Availability, Performance and Quality Rate - Akinnuli, Basil Olufemi (European Journal of Scientific Exploration, 2018)
This study investigates the production defectiveness of Ajaokuta Steel Rolling Mills company for twelve months prior to its short down. The causes of low efficiency were identified and solution for improvement were proffered. Also there were provided pieces of advises on how to avert future occurrence of same defectiveness. In Steel Rolling Mills a lot of evident losses were identified in this study. These losses (exactly 16) should be reduced greatly if not eliminated totally in order to improve the production effectiveness. The strategic decisions considered are: equipment availability, performance rate and quality rate. Each of these strategic decisions has its own attributes for computation. The product of these classified strategic decisions formed the Overall Production Effectiveness (OPE). The higher the OPE the better the company’s performance while the lesser it is the higher is the Overall Production Defectiveness (OPD). The data of twelve months of the company’s performance before short down in 2007 were collected and used to implement the model developed. The result showed that effectiveness of the company was 37% which means the Defectiveness Steel Rolling Mills was 67%. While the provided solutions to the elimination of such a high defectiveness level must decrease loses and increase effectiveness of work. This model will be a good decision tool for determining overall production effectiveness (OPE) as well as overall performance defectiveness (OPD) of a small medium and large scale industry.